Recent advances on anti-angiogenic multi-receptor tyrosine kinase inhibitors in osteosarcoma and Ewing sarcoma - Fleuren, Emmy D. G.; Vlenterie, Myrella; van der Graaf, Winette T. A. (Frontiers in Oncology, 2023)
Osteosarcoma (OS) and Ewing sarcoma (ES) are the two most common types of primary bone cancer that predominantly affect the young. Despite aggressive multimodal treatment, survival has not improved significantly over the past four decades. Clinical efficacy has historically been observed for some mono-Receptor Tyrosine Kinase (RTK) inhibitors, albeit in small subsets of OS and ES patients. Clinical efficacy in larger groups of OS or ES patients was reported recently with several newer generation multi-RTK inhibitors. All these inhibitors combine a strong anti-angiogenic (VEGFRs) component with simultaneous inhibition of other key RTKs implicated in OS and ES progression (PDGFR, FGFR, KIT and/or MET). However, despite interesting clinical data, none of these agents have obtained a registration for these indications and are thus difficult to implement in routine OS and ES patient care. It is at present also unclear which of these drugs, with largely overlapping molecular inhibition profiles, would work best for which patient or subtype, and treatment resistance almost uniformly occurs. Here, we provide a critical assessment and systemic comparison on the clinical outcomes to the six most tested drugs in this field in OS and ES to date, including pazopanib, sorafenib, regorafenib, anlotinib, lenvatinib and cabozantinib. We pay special attention to clinical response evaluations in bone sarcomas and provide drug comparisons, including drug-related toxicity, to put these drugs into context for OS and ES patients, and describe how future trials utilising anti-angiogenesis multi-RTK targeted drugs could be designed to ultimately improve response rates and decrease toxicity.